Five-years post commercial approval monitoring of eucalyptus H421 - Pinheiro, Ana Cristina; dos Santos, Anselmo Azevedo; Avisar, Dror; Gonsalves, José Mateus; Galan, Maria Paula; Abramson, Miron; Barimboim, Noga; Abrahão, Othon; Graça, Rodrigo Neves; Drezza, Thaís Regina; Silva, William (Frontiers in Bioengineering and Biotechnology, 2023)
Eucalyptus comprises the largest planted area of cultivated production forest in Brazil. Genetic modification of eucalyptus can provide additional characteristics for increasing productivity, protecting plant yield, and potentially altering fiber for various industrial uses. With this objective, a transgenic eucalyptus variety, event H421, received regulatory approval for commercial release after 6 years of approved risk assessment studies by the Brazilian National Technical Biosafety Commission (CTNBio) in 2015, becoming the first approved genetically modified (GM) eucalyptus in the world. GM event H421 enables increased plant biomass accumulation through overexpression of the Arabidopsis 1,4-β-endoglucanase Cel1, which remodels the xyloglucan–cellulose matrix of the cell wall during development to promote cell expansion and growth. As required, in that time, by the current normative from CTNBio, a post-commercial release monitoring plan for H421 was submitted, incorporating general surveillance for five consecutive years with the submission of annual reports. The monitoring plan was conducted on fields of H421 progenies, with conventional clones as comparators, cultivated in representative regions where eucalyptus is cultivated in the states of São Paulo, Bahia, and Maranhão, representing Southeast, Northeast, and Northern Brazil. Over the course of the five-year general surveillance monitoring plan for the approved GM eucalyptus H421, no adverse effect that could impact the biosafety of the commercially approved event was identified. Additionally, the GM eucalyptus exhibited behavior highly consistent with that of conventional commercial clones. Therefore, there was no need for an extra risk assessment study of a case-specific monitoring plan. The results show the importance of continuously updating the regulation norms of governmental agencies to align with scientific advances.